A meta-analysis of chemokines in alopecia areata: recruiting immune cells toward the hair follicle - Van Caelenberg, Elise; Belpaire, Arno; van Geel, Nanja; Speeckaert, Reinhart (Frontiers in Immunology, 2025)
A deeper understanding of the immune-based pathogenesis of alopecia areata is essential for the development of novel targeted therapies. Compared to cytokines, chemokines exhibit substantially higher serum concentrations, offering a more robust approach for large-scale immune profiling. However, the complexity of chemokine interactions presents challenges in defining their precise roles in AA. To explore these dynamics, we conducted a scoping review and meta-analysis of 46 original research articles examining chemokine expression in skin and blood samples from AA patients; meta-analysis was performed when three or more studies assessed the same chemokine in comparable groups. Th1-associated chemokines—including CXCL9, CXCL10, CCL5, and CXCL11—were consistently elevated in AA, reflecting the known IFN-γ–driven response. A distinct Th2 chemokine signature was also observed, with increased levels of CCL13, CCL17, CCL22, and CX3CL1. Additionally, elevated levels of CCL2, CCL3, CCL4 (monocyte/dendritic cell recruitment), and CCL11, CCL24, and CCL26 (eosinophil recruitment) suggest the involvement of immune pathways beyond classical T helper subsets. Meta-analysis confirmed significantly elevated serum levels of CXCL9 (p = 0.003), CXCL10 (p = 0.004), CXCL8 (p < 0.001), and CCL17 (p < 0.001). These findings reveal a complex chemokine profile in AA, dominated by Th1 activity but also implicating Th2 and other immune pathways, highlighting the potential benefit of broader immunomodulatory strategies to address the multifaceted immune dysregulation underlying the disease.